Hysteresis‐Free 1D Network Mixed Halide‐Perovskite Semitransparent Solar Cells. Issue 38 (24th August 2018) - Ka, Ibrahima; Asuo, Ivy M.; Basu, Suchismita; Fourmont, Paul; Gedamu, Dawit M.; Pignolet, Alain; Cloutier, Sylvain G.; Nechache, Riad
Abstract: The morphology of hybrid organic–inorganic perovskite films is known to strongly affect the performance of perovskite‐based solar cells. CH3 NH3 PbI3‐x Clx (MAPbI3‐x Clx ) films have been previously fabricated with 100% surface coverage in glove boxes. In ambient air, fabrication generally relies on solvent engineering to obtain compact films. In contrast, this work explores the potential of altering the perovskites microstructure for solar cell engineering. This work starts with CH3 NH3 PbI3‐ x Cl x, films with grain morphology carefully controlled by varying the deposition speed during the spin‐coating process to fabricate efficient and partially transparent solar cells. Devices produced with a CH3 NH3 PbI3‐ x Cl x film and a compact thick top gold electrode reach a maximum efficiency of 10.2% but display a large photocurrent hysteresis. As it is demonstrated, the introduction of different concentrations of bromide in the precursor solution addresses the hysteresis issues and turns the film morphology into a partially transparent interconnected network of 1D microstructures. This approach leads to semitransparent solar cells with negligible hysteresis and efficiencies up to 7.2%, while allowing average transmission of 17% across the visible spectrum. This work demonstrates that the optimization of the perovskites composition can mitigate the hysteresis effects commonly attributed to the charge trapping within the perovskite film. Abstract : The potential of altering perovskites microstructure through varying solution composition is studied for solar cell engineering. The introduction of different concentrations of bromide turns the film morphology into a partially transparent interconnected network of 1D microstructures which are used to fabricate semitransparent solar cells with negligible hysteresis, efficiencies up to 7.2% and an average transmission of 17% across the visible spectrum.